2021
DOI: 10.1001/jamaoto.2021.0930
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tracheostomy With Outcomes in Patients With COVID-19 and SARS-CoV-2 Transmission Among Health Care Professionals

Abstract: IMPORTANCE Approximately 5% to 15% of patients with COVID-19 require invasive mechanical ventilation (IMV) and, at times, tracheostomy. Details regarding the safety and use of tracheostomy in treating COVID-19 continue to evolve.OBJECTIVE To evaluate the association of tracheostomy with COVID-19 patient outcomes and the risk of SARS-CoV-2 transmission among health care professionals (HCPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 111 publications
1
36
2
6
Order By: Relevance
“…This is the largest and most comprehensive meta-analysis to date examining tracheostomy timing in patients with COVID-19. Unlike a meta-analysis included studies published before March 4, 2021 [ 50 ], we observed a decrease in time to ventilation weaning when patients underwent ET. This is most likely attributable to the addition of several studies after March 4, 2021.…”
Section: Discussioncontrasting
confidence: 79%
“…This is the largest and most comprehensive meta-analysis to date examining tracheostomy timing in patients with COVID-19. Unlike a meta-analysis included studies published before March 4, 2021 [ 50 ], we observed a decrease in time to ventilation weaning when patients underwent ET. This is most likely attributable to the addition of several studies after March 4, 2021.…”
Section: Discussioncontrasting
confidence: 79%
“…Recent systematic reviews have attempted to assess the utility of performing tracheotomy in the critically ill COVID-19 patient population [ 2 , 4 ]. While these suggest some potential benefits in terms of decreased ICU (intensive care unit) stay and overall mortality, the level of heterogeneity and possible selection bias leave interpretation of these results open.…”
Section: Utility Of Performing Tracheotomy In the Critical Care Covid-19 Populationmentioning
confidence: 99%
“… If a patient is COVID-19 positive and it has been less than 20 days since symptom onset or first positive RT-PCR, we recommend against performing a tracheotomy in this group of patients who are potentially still infectious [ 2 , 3 , 11 , 12 ]. This should only generally be considered in this situation if the endotracheal tube is proving insufficient to provide an adequate airway, or an emergent procedure is required [ 1 ].…”
Section: Changes To Previous Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations